Ürdün’de din eğitimi - Thalgi, Mohammad (My University, 2007)
ÜRDÜN’DE DİN EĞİTİMİ Bir ülkede uygulanan din eğitiminin özelliklerini ve toplumsal, kültürel ihtiyaçlarına cevap veren bir eğitim sistemini anlamak için, hem örgün eğitim hem de yaygın eğitimde din eğitimi unsurları incelenmelidir. Öyleyse bu tezin temel amacı, Ürdün’ün genel eğitim sisteminde, din eğitiminin nasıl öğretilip uygulandığı, ülkede din eğitiminin tarihi, hukuki durumları, devlet genel eğitim felsefesinde din eğitiminin yeri ve örgün-yaygın eğitimde din eğitimi unsurları nitelikleri olarak belirtilmeğe çalışmıştır. Araştırmada Ürdün’deki din eğitimiyle ilgili literatür ve kütüphane kaynaklarından yararlanılacaktır. Ayrıca gözlem ve görüşme metotlarından da istifade etmeye çalışmıştır. Osmanlı Ürdün coğrafyasını kapsayan Karek ve Horan sancaklarına, Maarif-i Umumiye Nezareti’nin belgelerinde yer verilmiştir. 22 tane kayıtlı İptidai okullar, 4 Rüştiye ve ayrıca 26 misyonerlik okulu bulunmuştur. Ürdün’ün eğitim tarihinde en önemli yasalar 1964 ve 1994 yıllarında çıkarılan kanunlardır. Bu kanunların genel eğitim anlayışında İslâmi hedefler bulunmaktadır. Ürdün eğitim aşamaları, anaokulu, 10 yıllık Temel eğitim aşaması ve iki yıllık lise aşaması olarak ayrılmaktadır. Anaokullarında din eğitimi dersleriyle ilgili belli bir program yoktur. Okullar kendilerine has özel bir programla din dersi okutabilirler. Temel eğitimde hem devlet hem de özel okullarda da, birinci sınıftan itibaren, haftada iki ders İslâm eğitimi ve bir ders de Kur’ân-ı Kerim okutulmaktadır. Akademi ve meslek Liselerinde de haftada üç ders, İslâm kültürü dersi okutulmaktadır. İslâm bilimlerinde ihtisas lisesi olarak Şer‘î lise bulunmaktadır. Akaid, fıkıh, Kur’ân ve hadis bilimleri ve İslâm bilimleri dersleri okutulmaktadır. Ürdün’de ilk Şeriat Fakültesi Ürdün ünitesinde 1971 yıllında kurulmuştu. 2005 yılına kadar Ürdün’de 8 Şeriat (ilahiyat) fakültesi bulunmaktadır. Ürdün hükümeti Ürdünlü Hıristiyanlara kiliseleri korumak, kiliselerinde dini faaliyetler yapmak, özel dini okullar kurmak ve içinde Hıristiyan din eğitimi dersleri okutulma gibi hakları tanımışlardır. Hıristiyanların din eğitimi kilise veya kendi okullarında okutulmaktadır. Yaygın din eğitimi düzenlenen kurumlar olarak Kültür Bakanlığına bağlı Kur’ân eğitim merkezlerinin “Cemiyetü’l-Mühafazati ale’l’l-Kur’âni’l-Kerim” ve Vakıflar Mukaddesât ve İslâm İşleri Bakanlığının düzenlediği faaliyetlerdir

RELIGIOUS EDUCATION IN JORDAN For any country, the characteristics of applied religious upbringing in formal or non-formal education is considered to be particularly important due to the extent that the private sector has influenced it. The fundamental objective of this dissertation is to elucidate the reality of religious upbringing in the Jordanian educational system; from the historical and legal perspective as well as its place in the state’s educational philosophy. Moreover, the particular features of the religious educational sources in formal and non-formal education are central to this discussion. This dissertation has benefited from the use of educational and historical literature which contains information of religious upbringing and likewise using methods of comparison, observation and description have been equally beneficial. During the Ottoman era, Jordan was administered by all those under the banners of Hovran and Karek. In this period, the historical documents recorded the existence of twenty two primary schools and four secondary schools in addition to the presence of twenty six missionary schools that focused on religious education. The legal state of education from the years 1964 to 1994 was the most important educational legislation in the history of the state and which was also geared towards the realization of Islamic educational objectives. The levels of education in Jordan were ordered so that there were two years of primary school education, ten years for the fundamental period and two years for the secondary school phase. There is no specific study for Islamic education at primary level schooling while some of the private schools organized a program containing a study of Islamic education in the basic teaching period from the first class to the tenth. The teaching completed two weekly sessions for the study of Islamic education and one weekly session for the recitation of the Noble Qur’an. In the phase of secondary academic and vocational teaching, there was also teaching of Islamic culture divided into three weekly sessions. With regards to the religious teaching in the phase of advanced training in Jordan, establishment of the first sharia’ college was undertaken in the University of Jordan from the years 1971 until 2005 with eight sharia’ colleges in total. The Jordanian government protected the rights of Jordanian Christians so as to provide freedom for organizing religious activities and the construction of Christian schools and the teaching of Christianity therein. With regards to non-formal education (not formal), for religious education, this is responsible for arranging everything (the society for the preservation of the Qur’an) that belongs to the ministry of culture and likewise the activities that are arranged by the ministry of religious endowments and Islamic affairs.
Keywords: Din Eğitimi_Ürdün; İslam Dini